Institutional Equity Trading Costs: NYSE Versus Nasdaq - Chan, Louis K.C.; Lakonishok, Josef (Journal of Finance, 1997)
We compare execution costs (market impact plus commission) on the New York Stock Exchange (NYSE) and Nasdaq for institutional investors. The differences in cost generally conform to each market's area of specialization. Controlling for firm size, trade size, and the money management firm's identity, costs are lower on Nasdaq for trades in comparatively smaller firms, while costs for trading the larger stocks are lower on NYSE. The cost differences estimated from a regression model are, however, sensitive to the choice of time period.